Wavelet analysis of MAXI J1535–571 with Insight-HXMT. Issue 4 (23rd May 2022) - Chen, X; Wang, W; You, B; Tian, P F; Liu, Q; Zhang, P; Ding, Y Z; Qu, J L; Zhang, S N; Song, L M; Lu, F J; Zhang, S
ABSTRACT: In this paper, wavelet analysis is used to study the spectral-timing properties of MAXI J1535–571 observed by the Hard X-ray Modulation Telescope ( Insight -HXMT). Low-frequency quasi-periodic oscillations (QPOs) are detected in nine observations. Based on wavelet analysis, the time intervals with QPOs and non-QPOs are isolated, and the corresponding spectra with QPOs and non-QPOs are analysed. We find that the spectra with QPOs (hereafter QPO spectra) are softer than those without QPOs (hereafter non-QPO spectra) in the hard intermediate state (HIMS), while in the soft intermediate state (SIMS), the QPO spectra are slightly harder. The disc temperature of the QPO regime is slightly lower during the HIMS, but becomes higher during the SIMS. The cutoff energies of QPO spectra and non-QPO spectra do not show significant differences. The flux ratio of the disc to total flux is higher for the time intervals with non-QPOs than that in the QPO regime. We propose that these differences in the spectral properties between QPO and non-QPO regimes could be explained through the scenario of Lense–Thirring precession, and the reversal of the QPO/non-QPO behaviour between the HIMS and SIMS may be associated with the appearance/disappearance of a type-B QPO, which might originate in the precession of the jet.